Deep-sea smelts, pencil smelts, and barreleyes (Teleostei: Argentiniformes) from oceanic islands and seamounts off northeastern Brazil. Issue 10 (25th November 2020) - Mincarone, Michael M.; Martins, Júlia R.; Di Dario, Fabio; Eduardo, Leandro N.; Frédou, Thierry; Lucena-Frédou, Flávia; Bertrand, Arnaud
ABSTRACT: New data on the taxonomic composition and distribution of rare deep-sea species of the Bathylagidae, Microstomatidae, and Opisthoproctidae (Argentiniformes) collected off northeastern Brazil, including the Rocas Atoll, the Fernando de Noronha Archipelago, and seamounts off Rio Grande do Norte State are provided. Collections were made by the French RV Antea during the ABRACOS 2 (Acoustics along the BRAzilian COaSt) expedition, between April 9 and May 6, 2017. Among the six species of argentiniforms identified, three are reported for the first time in Brazilian waters: Xenophthalmichthys danae (Microstomatidae), Opisthoproctus soleatus and Rhynchohyalus natalensis (Opisthoproctidae). Three additional species previously recorded off Brazil have their geographic distributions extended to the northeastern region of the country: Dolicholagus longirostris, Melanolagus bericoides (Bathylagidae), and Winteria telescopa (Opisthoproctidae). Remarks on other species of the Argentiniformes reported in the Brazilian Exclusive Economic Zone are also provided. A total of 11 genera and 14 species of the order are confirmed to occur in the region.